2014
DOI: 10.4278/ajhp.121012-quan-500
|View full text |Cite
|
Sign up to set email alerts
|

Objectively Measured Sleep Patterns in Young Adult Women and the Relationship to Adiposity

Abstract: Inconsistent sleep patterns and poor sleep efficiency are related to adiposity. Consistent sleep patterns that include sufficient sleep may be important in modifying risk of excess body fat in young adult women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 70 publications
4
45
0
1
Order By: Relevance
“…To evaluate potential body composition changes during the off-season and in-season, composition assessments took place at 3 . The off-season occurred between the ES and PS, and players partook in unmonitored training to help elicit the natural off-season training regimens and lifestyles of collegiate hockey players in Canada.…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate potential body composition changes during the off-season and in-season, composition assessments took place at 3 . The off-season occurred between the ES and PS, and players partook in unmonitored training to help elicit the natural off-season training regimens and lifestyles of collegiate hockey players in Canada.…”
Section: Experimental Approach To the Problemmentioning
confidence: 99%
“…Long practice days, substantial travel, demanding schedules, and game preparations all influence a collegiate-athlete's sleep, nutrition, training, and activity levels outside of their sport of choice, and can have an impact on their overall body composition (3,17,28,32). Although body composition can be reflective of many factors unrelated to elite sport, many recognize that this trait alone can be influential on the performance of elite athletes in competition (1).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep is a physiological necessity and its restorative properties are important for mental, emotional and physical health [1]. Disrupted sleep has been associated with respiratory illnesses, gastrointestinal disorders, diabetes, cardiovascular disease, depression, abnormal hormone and immune functioning, and cancer [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies found no association [13, 14]. A majority of studies examining these relationships utilized self-reported sleep duration, though several found associations of BMI with actigraphic-measured sleep [1, 9, 15, 16] or self-reported sleep quality [17]. However, more research is needed to fully understand how other actigraphic-based sleep measures are associated with body composition (e.g., sleep onset, wake time, wake-after-sleep-onset [WASO]), as these may represent different aspects of sleep compared to sleep duration.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly one recent survey evaluated the association between sleep duration, body weight and adiposity (Bailey et al, 2014). Among 330 young women (aged around 20), inconsistent sleep patterns and poor sleep efficiency were related to adiposity.…”
Section: Overweight Acts Mechanically By Mass Loading On the Upper Aimentioning
confidence: 99%